IBM (Meganyctiphanes norvegica and Thysanoessa raschii) -- DATASETS - Benkort Déborah; Maps Frédéric (Zenodo, 2018)
In this file are found the datasets used for the following study: Individual‐based modeling explains the contrasted seasonality in size, growth, and reproduction of the sympatric Arctic (Thysanoessa raschii) and Nordic krill (Meganyctiphanes norvegica) in the St. Lawrence Estuary, eastern Canada This study was published on 2018-09-14 (doi: 10.1002/lno.11032 ). The file MN_L&O_results.Rdata corresponds to the dataset for the Meganyctiphanes norvegica species, and the file TR_L&O_results.Rdatacorresponds to the dataset for the Thysanoessa raschii species.